2022
DOI: 10.1063/5.0074987
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear static and dynamic performance of CNT reinforced and nanoclay modified laminated nanocomposite plate

Abstract: Under static and dynamic loading circumstances, the mechanically and thermo-initiated nonlinear static and dynamic assessment of the bending response of single-walled carbon nanotubes’ (CNTs’) fibers with a nanoclay particle reinforced polymer hybrid laminated composite plate is investigated. To evaluate the effective elastic characteristics of the CNTs’ fibers on the nanoclay particle modified polymer hybrid laminated plate, a modified Halpin–Tsai method is applied in an orthotropic way. The theory of higher-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…F-statistic is a representation of joint variable comparison and its higher value (56. 30) is an evidence of statistical significance of the developed model. Similarly, higher t-values for feed and feed×feed indicate that the corresponding null hypothesis can be rejected, and the explanatory variables are significant, proving influence of feed rate on thrust force.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…F-statistic is a representation of joint variable comparison and its higher value (56. 30) is an evidence of statistical significance of the developed model. Similarly, higher t-values for feed and feed×feed indicate that the corresponding null hypothesis can be rejected, and the explanatory variables are significant, proving influence of feed rate on thrust force.…”
Section: Discussionmentioning
confidence: 89%
“…The extensive research in this field, as evidenced by studies such as those conducted by Bayraktar and Turgut [21], Kastabha et al [22], Raja et al [23], Mohan Kumar et al [24], and others [25][26][27][28][29][30][31], highlights the critical importance of understanding the effects of various drilling parameters. These studies have collectively advanced the knowledge of how factors like feed rate, cutting speed, drill geometry, and material composition influence drilling outcomes such as delamination, thrust force, surface roughness, and hole quality.…”
Section: Introductionmentioning
confidence: 99%
“…Omar Hamad at el. [41] analysed the influence of critical FDM process parameters such as layer thickness, air gap, build orientation, raster angle road width, and number of contours, on build time, feedstock material consumption and dynamic flexural strength [18], [33], [35], [42]- [45] using Qoptimal response surface methodology [10], [43], [46], [47]. They concluded that flexural strength or flexural modulus improves significantly using increased layer thickness [41].…”
Section: Response Surface Methodsmentioning
confidence: 99%
“…Drum brakes: The interior side of a revolving drum expands and rubs against the shoes or lining [34][35][36]. When braking, the shoe or brake lining expands or moves outward to attach itself to the brake drum, creating friction that slows or stops the drum from rotating.…”
Section: Introductionmentioning
confidence: 99%